Spindle Cell Carcinoma of the Tongue: Fallacies in Its Diagnosis - Smitha Chandra B.C, Rajeev Naik, Amrit Kaur Kaler, Shweta C, (International Journal of Innovative Research in Medical Science, 2018)
Spindle cell carcinoma is a rare aggressive biphasic tumor, composed of neoplastic proliferation of both epithelial (squamous) and spindle cell population. It constitutes about 1% of all oral cavity tumors 2a and is almost rare on the tongue; only few cases have been reported so far. This variant of squamous cell carcinoma, comprises major diagnostic problems due to its varied histomorphology and resemblance to sarcomatous lesion; hence diligent screening and IHC markers are mandatory for its diagnosis.